Organic Reactions 2014
DOI: 10.1002/0471264180.or085.01
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Amination of Aryl and Alkenyl Electrophiles

Abstract: The copper‐catalyzed arylation and vinylation of nitrogen nucleophiles is a highly versatile method for the construction of sp 2 C–N bonds. Copper‐catalyzed C–N bond formation has an extensive history and the field has been reinvigorated with the development of ligand‐promoted catalyst systems that provide general and effective reactions under relatively mild conditions. Copper promotes arylation and vinylation of a wide range of nitrogen nucleophiles, including amines, nitrogen heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 823 publications
0
27
0
1
Order By: Relevance
“…More modern variants based on extensive ligand development and mechanistic understanding have significantly enhanced the applicability of Ullmann-Goldberg-type C-N (as well as C-X) bond formation. [17][18][19][20][21][22] Nevertheless, despite notable advances and the potential advantages that can be afforded by Cu catalysis, the uptake and application of Ullmann-Goldbergbased approaches has been largely overshadowed by developments in Pd catalysis.…”
Section: C-n Bond Formation Via Nucleophile-electrophile Cross-couplingmentioning
confidence: 99%
“…More modern variants based on extensive ligand development and mechanistic understanding have significantly enhanced the applicability of Ullmann-Goldberg-type C-N (as well as C-X) bond formation. [17][18][19][20][21][22] Nevertheless, despite notable advances and the potential advantages that can be afforded by Cu catalysis, the uptake and application of Ullmann-Goldbergbased approaches has been largely overshadowed by developments in Pd catalysis.…”
Section: C-n Bond Formation Via Nucleophile-electrophile Cross-couplingmentioning
confidence: 99%
“…An increase in the bulkiness of the substituents at the bromine atom in isomeric 1-bromo-2-fluoro-3-(trifluoromethyl)benzene and 2-bromo-1-fluoro-4-(trifluoromethyl)benzene led to insignificant decrease in the yields of corresponding derivatives 22 and 23 (entries 9 and 10). The introduction of more sterically hindered compounds in which the trifluoromethyl group is in the ortho-position to bromine demanded an increase of the catalyst to 8 mol% and the products 24-26 were obtained in low yields (entries [11][12][13]. The analysis of the reaction mixtures by 1 H NMR showed that many side processes other than amination took place in these cases (see also Supplementary Information, Scheme S2, Tables S3 and S4).…”
Section: Catalytic Amination Of Halogeno(trifluoromethyl)benzenesmentioning
confidence: 99%
“…Palladium-catalyzed amination of (hetero)aryl halides is well-known and widely described in the literature [9][10][11]. During last decade, an important trend in the catalytic organic synthesis has been clearly exhibited, that is, the so-called renaissance of Ullmann chemistry, which is extremely important for the development of new strategies of C-N bond formation [12][13][14][15][16][17]. Our own interest in this field deals with the catalytic arylation and heteroarylation of polyamines [18,19] and adamantane-containing amines and diamines [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Tr ansition metal-mediated C-N cross-coupling is an essential synthetic method, used extensively throughout the chemical industry for the synthesis of pharmaceuticals,a gro-chemicals,n atural products,a nd materials. [1][2][3][4][5][6][7][8] Thed evelopment of new or improved processes for C À Nb ond construction remains acontinual inspiration for metal-based reaction development. Despite ab road diversity and subtlety in the mechanism of these methods,t he basic premise of the reaction involves as eries of individual mechanistic steps, e.g.,o xidative addition, transmetalation, and/or deprotonation, to allow access to akey metal complex bearing formally anionic, covalently bound C-and N-ligands (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%